Dekonstruksie en Bybelse hermeneutiek - Steenekamp, N. J. S. (Hervormde teologiese studies, 1991)
Deconstruction and biblical hermeneutics The purpose of this article is to evaluate deconstruction as a postmodern philosophical viewpoint in relation to biblical hermeneutics as a theological interpretation method. A short exposition of postmodernity is given to emphasise deconstruction’s aim of deconstructing traditional views on texts and metaphysics. This leads to intertextual reading which is in opposition to the textual reading of biblical hermeneutics. The consequences of deconstruction are finally evaluated in relation to the methods of Redaktionsgeschichte and the historische Jesus Forschung.